A methodology for binary encoding of citation metadata. (1st January 2012) - Poulos, Marios; Korfiatis, Nikolaos; Bokos, George
In this paper we describe a methodology for binary encoding of citation metadata which targets the problems of versioning generated from the function of the web agents and/or crawlers on which Google Scholar and Citeseer systems operate. Typically citation indexes require a period of time in order to index the cited articles and update their counters, which is a contingency to allow processing of information. Furthermore, the storage of this information is based on text form, which requires large storage space. The proposed method is an online system based on the existence of a central relational database (in binary format) and the existence of two automated procedures, which carry out the acts of publishing and citation. In particular a detached authority provides a database which stores in the proposed binary coded format all the citations that a new article makes at the time that it is published. The communication between the database and the users is enabled by the use of XML files which can be stored in memory, making computation easier.